Healing history, healing a nation: A prophetic practical pastoral ministry of care - Mkandla, Mabutho (HTS teologiese studies, 2020)
In the late 19th century, colonial powers sought to destroy the Mthwakazi or Ndebele state in what is now Matabeleland in the south west region of Zimbabwe, to subdue and dominate its people. The people of Matabeleland suffered heavy losses of cattle and land. Paradoxically, these injustices did not end with the collapse of colonialism. Since independence in 1980, the people of Matabeleland have been victims of political violence, which has left thousands dead and many without a livelihood. Nothing came of the promised reconciliation, justice, peace, national cohesion, progress and prosperity in the post-colonial Zimbabwe. To date the region of Matabeleland still suffers from political, cultural and socio-economic disadvantages that call for a prophetic practical pastoral ministry of care. A critical exploration of the way in which the history of the region was documented exposes it as a victim of the legacy of injustice and political violence. This has had the effect of undermining progress and peace not only in Matabeleland, but also in the entire country. There is a lack of national cohesion, and the consequence is the absence of a common national vision. Notwithstanding the general prevalence of political and socio-economic dire straits affecting the whole country, Matabeleland presents a unique case study. The Roman Catholic Church which has been present in the country since colonial times has been actively engaged in the political and socio-economic realities of the country. In view of this, this article investigates the role the Church can play in the healing of a broken nation, with a preferential focus on Matabeleland. It proposes a prophetic practical pastoral ministry of care in order not only to heal the afflicted but also that they may find solidarity and fellowship as citizens. Such a role should further encompass reconciliation, rebuilding the people’s confidence and advocacy for their political, cultural and socio-economic development and progress.